Rituals of separation:: Family members' narratives about burial in death by COVID-19 - Neto, Neemias Costa Duarte (2024)
The funeral rituals are considered social and psychic organizers for the experience of farewell, and important for the elaboration of meaning for the loss and resolution of mourning, and thus, needed some reconfiguration during the pandemicThis study aims to analyze the narrative of family members about burial in death by COVID-19. This is a qualitative, descriptive and analytical research. Data collection occurred between October 2020 to July 2021 in the municipalities of Maranhão: Imperatriz, Lago da Pedra, Zé Doca and São Luís. For qualitative data analysis, we used the thematic content analysis proposed by Minayo and the Theory of Social Representations addressed by Serge Moscovici. The sample was composed of 13 interviewees. Through the empirical analysis of the data it can be seen that the monetary value of the coffin is important to the family, as an external or concrete record of the importance of the deceased. The presence of only family members is not enough to bury the deceased, with the need for other people; moreover, not touching the dead body produces feelings of pain and sorrow. The separation rituals have undergone transformations to adapt to this new scenario, but they are still experienced to express and process the mourning. The rapid clinical evolution of the disease does not accompany the psychic time of the family member to process the loss, generating intense suffering. It was possible to understand the new forms of mourning experienced in this pandemic, contributing to systematize the performance of mental health professionals for a better understanding of psychological suffering.